Risk factors for prolonged length of stay after colorectal surgery - Lobato,Luiz Felipe de Campos (2013)
OBJECTIVE: Colorectal surgeons often struggle to explain to administrators/payers reasons for prolonged length of stay (LOS). This study aim was to identify factors associated with increased LOS after colorectal surgery. DESIGN: The study population included patients from the 2007 American-College-of-Surgeons-National-Surgical-Quality-Improvement-Program (ACS-NSQIP) database undergoing ileocolic resection, segmental colectomy, or anterior resection. The study population was divided into normal (below 75th percentile) and prolonged LOS (above the 75th percentile). A multivariate analysis was performed using prolonged LOS as dependent variable and ACS-NSQIP variables as predictive variables. P-value < 0.01 was considered significant. RESULTS: 12,269 patients with a median LOS of 6 (inter-quartile range 4-9) days were included. There were 2,617 (21.3%) patients with prolonged LOS (median 15 days, inter-quartile range 13-22). 1,308 (50%) were female, and the median age was 69 (inter-quartile range 57-79) years. Risk factors for prolonged LOS were male gender, congestive heart failure, weight loss, Crohn's disease, preoperative albumin < 3.5 g/dL and hematocrit < 47%, baseline sepsis, ASA class ≥ 3, open surgery, surgical time ≥ 190 min, postoperative pneumonia, failure to wean from mechanical ventilation, deep venous thrombosis, urinary-tract infection, systemic sepsis, surgical site infection and reoperation within 30-days from the primary surgery. CONCLUSION: Multiple factors are associated with increased LOS after colorectal surgery. Our results are useful for surgeons to explain prolonged LOS to administrators/payers who are critical of this metric.